Characterization of a new type of neuronal 5-HT G-protein coupled receptor in the cestode nervous system - Camicia, Federico (2021)
Cestodes are platyhelminth parasites with a wide range of hosts that cause neglected diseases. Neurotransmitter signaling is of critical importance for these parasites which lack circulatory, respiratory and digestive systems. For example, serotonin (5-HT) and serotonergic G-protein coupled receptors (5-HT GPCRs) play major roles in cestode motility, development and reproduction. In previous work, we deorphanized a group of 5-HT7 type GPCRs from cestodes. However, little is known about another type of 5-HT GPCR, the 5-HT1 clade, which has been studied in several invertebrate phyla but not in platyhelminthes. Three putative 5-HT GPCRs from Echinococcus canadensis, Mesocestoides vogae (syn. M. corti) and Hymenolepis microstoma were cloned, sequenced and bioinformatically analyzed. Evidence grouped these new sequences within the 5-HT1 clade of GPCRs but differences in highly conserved GPCR motifs were observed. Transcriptomic analysis, heterologous expression and immunolocalization studies were performed to characterize the E. canadensis receptor, called Eca-5-HT1a. Functional heterologous expression studies showed that Eca-5-HT1a is highly specific for serotonin. 5-Methoxytryptamine and αmethylserotonin, both known 5-HT GPCR agonists, give stimulatory responses whereas methysergide, a known 5-HT GPCR ligand, give an antagonist response in Eca-5-HT1a. Mutants obtained by the substitution of key predicted residues resulted in severe impairment of receptor activity, confirming that indeed, these residues have important roles in receptor function. Immunolocalization studies on the protoscolex stage from E. canadensis, showed that Eca-5-HT1a is localized in branched fibers which correspond to the nervous system of the parasite. The patterns of immunoreactive fibers for Eca-5-HT1a and for serotonin were intimately intertwined but not identical, suggesting that they are two separate groups of fibers. These data provide the first functional, pharmacological and localization report of a serotonergic receptor that putatively belongs to the 5-HT1 type of GPCRs in cestodes. The serotonergic GPCR characterized here may represent a new target for antiparasitic intervention.